Effects of irradiation on the activation energies of Li2B4O7 phases - Yavuz, H; Ceylan, M (Elsevier Science Sa, 1998)
The effects of X-ray irradiation on the activation energies of Li2B4O7 phase transitions have been investigated. Differential scanning calorimetry measurements were taken before and after irradiation. The activation energies of normal and irradiated Li2B4O7 are 233 kJ mol(-1) and 279 kJ mol(-1), respectively. (C) 1998 Elsevier Science S.A. All rights reserved.
Keywords: activation energy; Avrami exponent; isothermal kinetics; non-isothermal kinetics